Pelaksanaan Kegiatan Posyandu dalam Meningkatkan Kesehatan Batita di Tanjung Batang, Kapas, Inderapura Barat - Sari, Venta 'Yulia; Sri Hartati (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2019)
This study aims to study the implementation of Posyandu activities in improving toddler health through activities. This type of research is quantitative survey. They population is all of the people of Tanjung Batang Kapas who have toddlers with as many as 36 people, samples taken 100% of the population. The technique of collecting data uses a questionnaire. Data collection tool eses quationnaire sheets. The data analysis technique uses the percentage formula. The results of the research show how the implementation of Posyandu activities in improving toddler health in Tanjung Batang Kapas, west Inderapura through activities (a) weighing the implemetantion sometimes and never, (b) assistance with complementary food for ASI and Vitamin A is done sometimes and never even, (c) supplementary feeding for underweihght children and growth is not enough sometimes and never, (d) immunization is done sometimes and never even, (e) monitoring the incidence of ISPA and diarrhea programs sometimes and never, also seen from (f) the healthof children (healthy children), there are still many children experiencing health problems so that they are categorized as less healthy children.